Changes in the Leaf Physiological Characteristics and Tissue-Specific Distribution of Ginsenosides in Panax ginseng During Flowering Stage Under Cold Stress - Zhang, Tao; Chen, Changbao; Chen, Yuqiu; Zhang, Qinghe; Li, Qiong; Qi, Weichen (Frontiers in Bioengineering and Biotechnology, 2021)
Panax ginseng is a valuable traditional Chinese medicine material with numerous applications. Ginsenosides are the key bioactive compounds in ginseng, and cold stress could influence their biomass and biosynthesis in ginseng tissues as stress tolerance mechanisms. In this study, using biotechnology to explore ginsenosides and their biosynthetic pathways，ginsenoside concentrations were evaluated over the short and long term under cold stress during P. ginseng flowering period. Cold stress significantly reduced ginseng biomass (root fresh weight and dry weight), and increased malondialdehyde, proline, soluble sugar, and soluble protein concentrations under short-term cold stress. Superoxide dismutase, peroxidase, and catalase activities also increased significantly under cold stress. With prolongation of the cold stress period, all antioxidant enzyme activity decreased. Protopanaxatriol (PPT)-type ginsenoside concentrations in taproots (phloem and xylem) and fibrous roots, as well as protopanaxadiol (PPD)-type ginsenosides in leaves increased significantly under short-term cold stress. The key genes SE, DS-Ⅱ, CYP716A52v2 and CYP716A53v2 involved in the ginsenoside biosynthesis pathway were significantly positively correlated with ginsenoside accumulation trends. Thus, short-term cold stress can stimulate membrane lipid peroxidation, in turn stimulating the antioxidant enzyme system to alleviate oxidative damage, and the expression of key enzyme genes involved in ginsenoside biosynthesis. The secondary metabolism of ginsenosides observed in the present study is a trade-off mechanism to facilitate adaptation to low temperature stress. During agricultural production, PPD/PPT ratio could be manipulated by low-temperature storage or treatment. In addition, ginseng cultivation activities should be conducted in areas with relatively low average annual temperatures, and shorter cultivation periods should be adopted to enhance ginsenoside yields.